Produção de nastúrcio em cultivo hidropônico com diferentes soluções nutritivas - Melo, Evanisa Fátima Reginato Quevedo (2006)
The nutrition, medicinal, and ornamental properties of the Tropaeolum majus L. has been a new object of interest in the nutritious and pharmaceutical areas. Two experiments were carried out with Nasturcio in hidroponic system Departamento of Fitotecnia at Universidade Federal de Santa Maria and Fazenda Tanabe in Mato Castelhano, Brazil. The objetive of the experiment I was to characterize the growing and production of Nasturcio (Tropaeolum majus L.) plants in hydroponics, that was carried out in polyethylene greenhouse. The experiment was developed in the Departmento de Fitotecnia, Núcleo de Pesquisa of Ecofisiologia and Hidropona (NUPECH), of the Universidade Federal of Santa Maria, RS, Brazil, from April to June 2003. A 3X11 factorial design, with six replicates, was used. The treatments were three nutrition solutions: Hoagland and Arnon (1950), Castellane and Araújo (1995), and Furlani (1995) combined with eleven periods of evaluation. Seedling were transplanted 21 days after the emergency and the phenometric measurements were done each seven days. The last sampling period was 77 days after transplantation (total of 91 days). The evaluated plants were divided on leaves, stalk, roots, and flowers in order to measure their dry and wet weight. The blowing period started when the plants were 49 days old. The plants showed a good growing in the hydroponics solution. The dry and wet matter productions, the plant height, and the number of leaves were crescent during the plant cycle. Biologic yield, foliar indexes, and growing rate of Nasturcio were greater at 49 days after the transplantation, and it relationship with days after the transplantation was linear. There was no difference among the nutrition solutions, although Furlani (1995) solution was the most economically. The second experiment was located in the Fazenda Tanabe, of Mato Castelhano, RS, Brazil, with the aim to evaluate the influence of cultivation systems and origins of seedlings in the evolution and partition of fresh and dry biomass of Nastúrcio cultivated in hidroponics, from October 2003 to March of 2004. A 2x2x6 factorial design. The treatments were constituted of two cultivation systems: profiles hidroponics and vases with commercial substratum; two origins of seedlings: foam fenolic and trays of 128 cells filled out with commercial substratum; and five evaluation times. The fresh and dry biomass of stem had larger increment to 75 DAT in the system of cultivation profile hidroponics with originated seedlings of foam fenolic. The biologic yield, foliar indexes, and growing rate of Nasturcio were greater at 45 days after the transplantation, and it relationships with days after the transplantation. The Nasturcios edible flowers showed low caloric value and high content of vitamin C.